Public relations: Theorizing the contestation of security technology. (December 2019) - Monsees, Linda
This article contributes to the emerging literature on publics within critical security studies. Its particular focus is on contestation in the context of diffuse security technology. Contemporary security practices are characterized by diffusion and dispersion. As a result, contestation of security technology is also dispersed and diffuse and requires an account of publics that is sensitive to this aspect. The article conceptualizes 'multiple publics' as a mode of fundamental contestation of established political institutions. In order to do so, it discusses previous approaches to sociotechnical controversies and material participation. As a result of this discussion, it becomes apparent that we need a concept of publics that does not reduce political contestation to a pre-existing set of institutions. I develop a notion of publicness that emphasizes the way in which publics are embedded in societal struggles. This is achieved by reading John Dewey as a theorist to whom contestation is a vital part of democracy. It becomes possible to understand contestation against diffuse security practices – such as surveillance – as forms of emerging publics, even though they might not feed back into governmental decisionmaking.